2016
DOI: 10.3390/rs8030220
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Settlement Expansion and Urban Growth Modelling Using Geoinformation for Assessing Potential Impacts of Urbanization on Climate in Abuja City, Nigeria

Abstract: This study analyzed the spatiotemporal pattern of settlement expansion in Abuja, Nigeria, one of West Africa's fastest developing cities, using geoinformation and ancillary datasets. Three epochs of Land-use Land-cover (LULC) maps for 1986, 2001 and 2014 were derived from Landsat images using support vector machines (SVM). Accuracy assessment (AA) of the LULC maps based on the pixel count resulted in overall accuracy of 82%, 92% and 92%, while the AA derived from the error adjusted area (EAA) method stood at 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 55 publications
(60 reference statements)
4
33
2
Order By: Relevance
“…The ML approach is one of the classical parametric statistical classifiers and is widely used for LULC classification [53]. Several studies have also evaluated alternative, recently-developed machine-learning algorithms for land-cover classification, such as support vector machine (SVM) methods [54], decision trees (DT) [55], and random-forest models (RF) [56,57]. Schneider [55] observed that the DT and SVM classifiers outperformed the ML classifier in the context of highly dynamic land-cover change and 'fuzzy' multi-signal classes around the Chinese cities of Chengdu, Xi'An, and Kunming.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…The ML approach is one of the classical parametric statistical classifiers and is widely used for LULC classification [53]. Several studies have also evaluated alternative, recently-developed machine-learning algorithms for land-cover classification, such as support vector machine (SVM) methods [54], decision trees (DT) [55], and random-forest models (RF) [56,57]. Schneider [55] observed that the DT and SVM classifiers outperformed the ML classifier in the context of highly dynamic land-cover change and 'fuzzy' multi-signal classes around the Chinese cities of Chengdu, Xi'An, and Kunming.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…To evaluate the consequences of urbanization and the validity of possible NBS, social and environmental scientists are increasingly using highly detailed LULCC models [11,12]. Landcover models have been used to address general questions of landcover change and urbanization around the world [2,9,10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]; however, only one other study models LULCCs under GI policies [28]. To predict precise landcover transitions and to answer specific questions of policy, future LULCCs need to be modeled at finer scales.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Lee [76] evaluated the SVM algorithms for landslide vulnerability mapping in the Gangwon province of Korea and the results suggested that SVM was quite suitable for a wide range of classification problems, even if the problems were of high dimension and were non-linear separable. Moreover, the approach was applied by Mahmoud et al [71] to monitor urbanization in Abuja, Nigeria. Schneider [70] evaluated the maximum likelihood classifier (ML), decision tree (DT), and SVM algorithms for monitoring land-cover change in urban and peri-urban areas using Landsat satellite data.…”
Section: Pre-processing Of Images and Design Of Image Classificationmentioning
confidence: 99%
“…A supervised approach support vector machines (SVM) classifier [18,70] was employed for the classification of LULC and change analysis. Several previous authors have evaluated the performance of SVM algorithms and concluded that it is one of the flexible supervised classifier options with high accuracy [68,[70][71][72][73][74]. SVM is a supervised, non-linear, non-parametric classification technique that is widely used in the remote sensing field due to its specific capability to draw conclusions even with limited training samples [75].…”
Section: Pre-processing Of Images and Design Of Image Classificationmentioning
confidence: 99%